Tubular wells water quality in Iguatama, Minas Gerais, Brazil - Souza, Otaviano Teodoro; Frade, Paulo Ricardo; Soares, Carolina Adélia da Silva Paim (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The high population growth coupled with increased waste generation has modified the quality and availability of both surface and groundwater. This study aims to verify the water quality and the treatment system efficiency implanted in different points of underground water abstraction in the municipality of Iguatama, Minas Gerais. Eight distinct collection points were defined, with the help of local water service sanitation provider (SAAE), which established a route for the collection, according to their importance level for the population, being five tubular wells in urban areas and three in rural areas. The analyzes were performed in the SAAE laboratory of Córrego Fundo-MG. The physical-chemical parameters analyzed were: residual chlorine, pH, turbidity and color. The microbiological parameters were: total coliforms, Escherichia coli and heterotrophic bacteria. The analyzes results demonstrated compliance with the potability standards established by the legislation and the treatment proved to be efficient at all collected points. No significant differences were found between the urban and rural areas, demonstrating that there is no association of results obtained with these sites. The municipality is concerned with maintaining water quality as well as all the care around the points such as enclosure and sanitation, which favors a better water quality.